Factors associated with veterinarians’ perceptions about the misuse of antibiotics and areas for improvement in small and medium-scale dairy farms in Mexico - Espinosa-Martínez, Mario Alfredo; Estrada-Cortés, Eliab; Villagómez Amezcua-Manjarrez, Eugenio; Cabrera-Torres, Eduardo José; Montiel-Olguín, Luis Javier (Acta Universitaria, 2026)
The objective was to analyze veterinarians’ perceptions of the inappropriate use of antibiotics in small and medium-scale dairy farms in Mexico and to identify factors that influence these perceptions. A structured questionnaire was applied to 75 technical advisors; 33 met the inclusion criteria (being a veterinarian, working with dairy cattle, and serving farms with up to 100 cows). Descriptive statistics and Fisher’s exact test were performed. Veterinarians estimated that 28.3% of their clients overuse antibiotics. Those who dedicate less time to dairy cattle identified higher inappropriate use of antibiotics (p = 0.02). An association was also found between concern about bacterial resistance and the perception that antibiotic use poses a public health threat (p = 0.009). It is concluded that about one third of producers may be using antibiotics inappropriately, highlighting the importance of strengthening technical advice and promoting preventive management practices.